Intelligent Computing Theories 9th International Conference, ICIC 2013, Nanning, China, July 28-31, 2013. Proceedings - Huang, De-Shuang.; Bevilacqua, Vitoantonio; Figueroa, Juan Carlos; Premaratne, Prashan; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed conference proceedings of the 9th International Conference on Intelligent Computing, ICIC 2013, held in Nanning, China, in July 2013. The 74 revised full papers presented were carefully reviewed and selected from numerous submissions and are organized in topical sections on neural networks, nature inspired computing and optimization, cognitive science and computational neuroscience, knowledge discovery and data mining, evolutionary learning and genetic algorithms machine learning theory and methods, natural language processing and computational linguistics, fuzzy theory and models, soft computing, unsupervised and reinforced learning, intelligent computing in finance, intelligent computing in petri nets, intelligent data fusion and information security, virtual reality and computer interaction, intelligent computing in pattern recognition, intelligent computing in image processing, intelligent computing in robotics, complex systems theory and methods.
Neural Networks -- Nature Inspired Computing and Optimization -- Cognitive Science and Computational Neuroscience -- Knowledge Discovery and Data Mining -- Evolutionary Learning and Genetic Algorithms -- Machine Learning Theory and Methods -- Natural Language Processing and Computational Linguistics -- Fuzzy Theory and Models -- Fuzzy Systems and Soft Computing -- Unsupervised and Reinforcement Learning -- Intelligent Computing in Finance/Banking -- Intelligent Computing in Communication Networks -- Intelligent Computing in Network Software/Hardware -- Intelligent Image/Document Retrievals -- Intelligent Data Fusion and Information Security -- Intelligent Prediction and Time Series Analysis -- Intelligent Sensor Networks -- Intelligent Fault Diagnosis -- Virtual Reality and Human-Computer Interaction -- Intelligent Computing in Robotics -- Intelligent Computing in Computer Vision.
Keywords: Computer science; Artificial intelligence; Computer vision; Optical pattern recognition; Bioinformatics; Computer Science; Artificial Intelligence (incl. Robotics).; Image Processing and Computer Vision; Pattern Recognition; Computational Biology/Bioinformatics.; Information Systems Applications (incl. Internet).; Computation by Abstract Devices